Sports in society issues and controversies - Coakley, Jay J. Ph. D. (New York, NY McGraw-Hill LLC, 2021)
"For over 30 years, Sports in Society has been a resource in the cultural, interactional, and structural dimensions of sports. The Thirteenth Edition provides a thorough introduction to the sociology of sport by raising critical questions to explore the relationships between sports, culture, and society. This text takes an issues-oriented approach to the study of sports in society and encourages the discussion of current sports-related controversies" -- Provided by publisher
Chapter 1. The Sociology of Sport: What Is It and Why Study It? -- Chapter 2. Producing Knowledge About Sports in Society: How Is Knowledge Produced In the Sociology of Sport? -- Chapter 3. Sports and Socialization: Who Plays and What Happens to Them? -- Chapter 4. Sports for Children: Are Organized Programs Worth the Effort? -- Chapter 5. Deviance in Sports: Is It Out of Control? -- Chapter 6. Violence in Sports: Does It Affect Our Lives? -- Chapter 7. Gender and Sports: Is Equity Possible? -- Chapter 8. Race and Ethnicity: Are They Important in Sports? -- Chapter 9. Social Class: Do Money and Power Matter in Sports? -- Chapter 10. Age and Ability: Barriers to Participation and Inclusion? -- Chapter 11. Sports and the Economy: What Are the Characteristics of Commercial Sports? -- Chapter 12. Sports and the Media: Could They Survive Without Each Other? -- Chapter 13. Sports and Politics: How Do Governments and Global Political Processes Influence Sports? -- Chapter 14. Sports in High School and College: Do Competitive Sports Contribute to Education? -- Chapter 15. Sports and Religions: Is It a Promising Combination? -- Chapter 16. Sports in the Future: What Do We Want Them to Be?
Includes bibliographical references and indexes
Keywords: Sports -- Psychological aspects; Sports -- Social aspects